ДЖОРДЖ ЭЛИОТ И ДЭВИД ГЕРБЕРТ ЛОУРЕНС: ТАК ЛИ ДАЛЕКИ ВИКТОРИАНСТВО И МОДЕРНИЗМ? (Filološke studije, 2019)
The author deals with a very difficult substance of aesthetic connections of one of the most Victorian writers, who is supposed to express the quintessence of the High Victorianism as the system of views, and at the same time the most furious of all Victorian writers polemicists with this system, and one of those writers, who intended his creative work and the ideology on the whole to overthrow old-fashioned views with their deep roots in the Victorian Age. The essays shows some very subtle and sometimes not too obvious “lessons” in character-making, psychological deepening in characters, representations of integral conception of a human being and masterfully depicted main characters’ search for the inner identity, which Lawrence gets while reading and thinking of George Eliot’s great novels. The author does it when appealing to some pieces of prose of both writers, and to their letters, literary essays and witnesses of the contemporaries.